2021
DOI: 10.15575/ijhar.v3i1.11119
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Halal Tourism Ecosystem Model in Borobudur Temple as Tourism Area

Abstract: Borobudur as one of the top wonderful destinations in the world is challenged to become one of halal tourism destinations in Indonesia. The purposes of this research are to find out and to launch the implementation of halaltourism ecosystem model in Borobudur Temple as tourism area in Indonesia. This research used a descriptive method. The researcher investigated the implementation of halal tourism ecosystem model in the Borobudur temple as tourism area by examining the variables of halal tourism ecosystems. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Considering there is still a lack of knowledge and implementation of halal tourism in Indonesia. For example, Borobudur, one of the super priority tourist destinations, is still not optimal in implementing tourism policies based on halal tourism [19].…”
Section: Ideate Game Design Prototype and Test Indonesian Tourismmentioning
confidence: 99%
“…Considering there is still a lack of knowledge and implementation of halal tourism in Indonesia. For example, Borobudur, one of the super priority tourist destinations, is still not optimal in implementing tourism policies based on halal tourism [19].…”
Section: Ideate Game Design Prototype and Test Indonesian Tourismmentioning
confidence: 99%
“…It is hoped that the improving quality of human resources will have an impact on tourism development and increase aggregate economic added value. In the analysis of competitiveness on the Human Resources Index indicator, several regions also found that had high competitiveness, including Garut Regency, Pangandaran Regency and others (Brata & Pemayun, 2018;Sutono et al, 2021;Uyar et al, 2023).…”
Section: Competitiveness Of Human Resources Indexmentioning
confidence: 99%
“…34 Lukman Hakim dengan judul "Gubernur Khofifah Siapkan Kawasan Pesisir Jadi Desa Wisata Halal", dalam https://daerah.sindonews.com/ accessed Desember 12, 2021 utilitarianism, the legal policy aims to provide the most significant benefit and happiness to as many people as possible. 40 Realizing sustainable halal tourism requires an integrated pentahelix collaboration involving various sectors and stakeholders. The collaboration must start with spatial planning, calculation of carrying capacity (ecological carrying capacity, physical carrying capacity, and social carrying capacity), AMDAL studies, use of natural resources in an environmentally friendly manner, as well as the roles and responsibilities of each stakeholder involved in the halal tourism development.…”
Section: Iqtishadia: Jurnal Ekonomi Dan Perbankan Syariahmentioning
confidence: 99%